2001
DOI: 10.1001/archinte.161.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Folic Acid Supplementation and Serum Homocysteine Levels

Abstract: A dosage of folic acid of 0.8 mg/d appears necessary to achieve the maximum reduction in serum homocysteine level across the range of homocysteine levels in the population. Current US food fortification levels will achieve only a small proportion of the achievable homocysteine reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
3
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 21 publications
6
93
3
4
Order By: Relevance
“…The fact that both filtered and unfiltered coffee are associated in a dose-response manner with tHcy makes diterpenes (which are occurring at higher concentrations in unfiltered coffee, Bak, 1990) a less likely causal factor. These consistent findings also raised the question whether it is possible to reduce the coffee-induced tHcy increase by agents known to reduce homocysteine such as folic acid or pyridoxine (Mansoor et al, 1999;Wald et al, 2001).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The fact that both filtered and unfiltered coffee are associated in a dose-response manner with tHcy makes diterpenes (which are occurring at higher concentrations in unfiltered coffee, Bak, 1990) a less likely causal factor. These consistent findings also raised the question whether it is possible to reduce the coffee-induced tHcy increase by agents known to reduce homocysteine such as folic acid or pyridoxine (Mansoor et al, 1999;Wald et al, 2001).…”
Section: Introductionmentioning
confidence: 78%
“…The dosage of folic acid supplement was set to 200 mg/day, which corresponds to a change in homocysteine levels of 0.1-2.5 mmol dependent on initial tHcy levels (Wald et al, 2001). The current recommendation of folic acid in Sweden is 300 mg/day for the general population, and 400 mg for pregnant women (Swedish Recommended Allowances, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…While this appears to be the most likely explanation of the differences in response of tHcy between the study by Malinow et al (1998) and our own study, it should also be noted that participants in the Malinow study were older individuals with ischaemic heart disease while those in the Ward et al (1997) study and our own study were younger and free of clinical disease. Indeed, Wald et al (2001) found that patients with ischemic heart disease required daily doses of folic acid of up to 800 mg to optimally lower tHcy.…”
Section: Discussionmentioning
confidence: 99%
“…24 Such a reduction in homocysteine would be achievable by folic acid supplementation of 0.8 mg day À1 . 25 Other studies, however, have suggested that folic acid intervention, in the presence and absence of vitamin B 6 , does not lower the risk of recurrent cardiovascular disease or death after acute myocardial infarction. 26 This finding is mirrored in studies in which patients with vascular disease showed no decrease in the risk of major cardiovascular events after supplementation with folic acid and vitamin B 6 and B 12 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%